PENERAPAN ICE BREAKING DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SEKOLAH DASAR - Fadillah Quraini, Annisa; Mega Diana, Siska; Kembar Habibi, Roy; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The saturation and decrease in the focus of students during learning Indonesian becomes one of the challenges faced by educators in elementary school. This research aims to describe the application of ice breaking in Indonesian language learning in grade IV of State Elementary School 7 Eastern Metro as well as the factors that affect its implementation. The research uses qualitative methods with a case study approach. Data was collected through observation, interview, and documentation. Research results show that ice breaking is done when students start to lose focus or show signs of saturation. The activities used are in the form of clapping, singing, and simple games that help create a more active and fun learning atmosphere. Factors that affect the implementation include student interest, learning conditions, educator creativity, differences in student character, and limited learning time.